(3eSfO YHO Gddg Hf CHj Chais - (3CHh eMeO jMji Hf eMeO Hf UGYOs
(3ChdgG (B:s
(3CNHQfG TjNfG fLjH GdOjf CHh GdaQL YHO GddWja GdMQGfi bGd MOjK GdbGSe Hf Yha GdTjHGfi Yf YHO Gddg Hf CHj Chai s
(3BNQgG (B:s
(3Yf YHO Gddg Hf CHj Chai bGd (B: (3fgi QShd Gddg Udi Gddg Ydjg hSde Yf fHjP GdLQ BNQ eSfO YHO Gddg Hf CHj Chai s
(3HgG fXGe GdJYbjHIs
(3QhGjI CHj GdbGSe YHjO Gddg Hf eMeO Hf ESMGb Hf UHGHI GdHRGR HBNQgG SeGYGJ HYVgG SfI (B731 (3hHYVgG SfI (B777 (3Ke SeGYGJ efbhdI ef GdCUd GdefJSN efgs
(3cJHJ HNW bdjd GdfbWs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeMehOjI (B- (3HecJHI GdeOjfI GdefhQI GdYGeI(B((3eLGejY (B124) s
Keywords: (3GdMOjK h GdeUWdMs